Pengaruh Work Life Balance, Lingkungan Kerja, dan Organizational Citizenship Behavior terhadap Loyalitas Karyawan di PT Alendors Global Production - Rika Fitri Alfiani; Ridlwan Muttaqin (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
In today’s workplace, organizational success is highly dependent on internal factors, particularly employee loyalty. Preliminary observations at PT Alendors Global Production indicate a decline in employee loyalty, which has led to an increase in turnover rates. This condition is driven by challenges in maintaining work–life balance, an unconducive work environment, and the need to enhance Organizational Citizenship Behavior (OCB). This study aims to quantitatively examine and analyze the partial and simultaneous effects of Work–Life Balance (WLB), Work Environment, and Organizational Citizenship Behavior (OCB) on employee loyalty at PT Alendors Global Production. The research employs a quantitative approach using a causal associative method, with a population of 80 employees of PT Alendors Global Production as respondents. Data were collected through observation and questionnaire distribution and analyzed using multiple linear regression with the assistance of SPSS version 26. The partial regression analysis results indicate that Work–Life Balance and Work Environment have a positive and significant effect on employee loyalty. Conversely, Organizational Citizenship Behavior (OCB) shows a statistically insignificant effect. However, the simultaneous test (F-test) reveals that the three independent variables collectively have a significant contribution to employee loyalty, with an R-squared value of 0.553, indicating that 55.3% of the variation in employee loyalty is explained by the combined influence of these variables. These findings conclude that efforts to enhance employee loyalty largely depend on fulfilling work–life balance and providing a supportive work environment. Therefore, it is recommended that organizations focus their strategies on improving WLB policies and creating a safe and conducive work environment to strengthen employees’ emotional attachment and long-term loyalty.